The Ideal Body Construction and Beauty Myths in the Uglies 2024 Film - Ainun Azizah; Ade Kusuma (International Journal of Social, Economic, and Business, 2026)
Film is a mass media that is not only used to deliver information but also to construct social reality through audio and visual elements that can shape viewers’ perceptions. Film can be a medium for constructing beauty myths that equate women’s physical appearance with their self-worth. The film Uglies (2024) depicts a future phenomenon where plastic surgery is mandatory as a prerequisite for social acceptance. This study aims to examine the discourse of beauty standards in the film through the positions of subject-object and audience. The method used is descriptive qualitative with Sara Mills’ critical discourse analysis approach. The results show that: 1) Uglies 2024  represents beauty standards as a tool of social control to regulate women. 2) Women are positioned as passive objects who lose their rights to their own identities due to the pressure of authority. Beauty standards become a measure of self-worth that deprives women of their freedom as a result of forced standardization by those in power. This study also explains that film serves as a critical reflection on the role of media in shaping unrealistic beauty standards that impact freedom and the way individuals perceive themselves.